The role of tetradecane in the identification of host plants by the mirid bugs Apolygus lucorum and Adelphocoris suturalis and potential application in pest management - Yin, Haichen; Li, Wenjing; Xu, Min; Xu, Dong; Wan, Peng (Frontiers in Physiology, 2022)
The mirid bugs Apolygus lucorum and Adelphocoris suturalis are considered serious pests of many crops in China, the host plant recognition of these pests remains unclear. The current study investigated the vital odor cues of two mirid bugs and evaluated the role of olfactory recognition in host recognition. The GC-EAD response of mirid bugs to volatiles of their host plant Phaseolus vulgaris was tested. Tetradecane, 2-propyl-1-pentanol, and dodecanal elicited strong EAG responses by mirid bugs and were tested with field experiments. The results indicated tetradecane was significantly more attractive than other attractants, yielding 30.33 ± 2.19 mirid bugs trapped during seven days. The selected response rates to tetradecane were above 60%, which was most attractive to female A. lucorum at 1.5 mg/mL. Among seven tetradecane derivatives, tetradecane and tetradecanoic acid were the most potent attractants to A. lucorum and A. suturalis. Tetradecane was present in the volatiles of 10 common hosts, and their difference in relative content was significant. The presence of tetradecane seemed relevant to the olfactory response intensity of two mirid bugs towards the different host plants. The artificial supplement of tetradecane increased the attractive effect of host plants. These results suggested that tetradecane plays a vital role in the olfactory selection by two mirid bugs, and it can be made into field baits as a novel ecological strategy to manage these pests with widely reported pesticide resistance. However, results suggested host recognition is not entirely dependent on odor cues. We demonstrated that A. suturalis and A. lucorum adults have similar olfactory recognition mechanisms to their hosts in long-distance host selection. While, the differences in host plant selection between the two pests should occur in close range due to differences in gustatory or tactile sensory organs of A. lucorum and A. suturalis.